2018
DOI: 10.1021/acsami.7b13444
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Effect of Intramolecular Charge Transfer on the Light Emitting Properties of BODIPY

Abstract: A new way to approaching highly emissive BODIPY dyes in both solution and solid state is achieved by introducing intramolecular charge transfer (ICT). A hybrid excited state that shows behaviors of both the ICT excited state and local excited state is discovered to be beneficial in avoiding the disturbance from the rotation vibration of the flexible phenyl substituents. Thus, the nonradiative transition process is suppressed, and the fluorescence efficiency goes up. By modification of the excited state, we rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…The radiative rate constant ( k RAD =Φ F /τ S =1×10 8 s −1 ) is in good agreement with that ( k SB =1.3×10 8 s −1 ) calculated from the Strickler–Berg expression . Of the literature reports referring to fluorescence from related B‐aryl BODIPY fluorophores, two describe strong emission in fluid solution but a third details weak fluorescence at room temperature . This latter report mentions that emission is recovered in a frozen glass at 77 K.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The radiative rate constant ( k RAD =Φ F /τ S =1×10 8 s −1 ) is in good agreement with that ( k SB =1.3×10 8 s −1 ) calculated from the Strickler–Berg expression . Of the literature reports referring to fluorescence from related B‐aryl BODIPY fluorophores, two describe strong emission in fluid solution but a third details weak fluorescence at room temperature . This latter report mentions that emission is recovered in a frozen glass at 77 K.…”
Section: Resultssupporting
confidence: 82%
“…As reported for a related compound by Gao et al., 2 is strongly fluorescent in an optical glass at 80 K. Indeed, in 2‐methyltetrahydrofuran (MTHF), which forms a hard glass below 100 K, the fluorescence yield depends markedly on temperature (Figure ). At 80 K, Φ F approaches unity while τ S has a value of 6.5±0.1 ns.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…It was found that APTC has excellent optical properties such as aggregation‐induced emission enhancement (AIEE) and intramolecular charge transfer (ICT) due to its D‐π‐A structure. It meant that APTC not only was more conducive to fluorescence imaging in living cells, but also had potential applications in many fields such as OLEDs, stimuli‐responsive smart materials and organic semiconductors …”
Section: Background and Originality Contentmentioning
confidence: 99%